2005
DOI: 10.1016/j.ejheart.2005.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials update from the American Heart Association: REPAIR‐AMI, ASTAMI, JELIS, MEGA, REVIVE‐II, SURVIVE, and PROACTIVE

Abstract: This article provides information and a commentary on trials presented at the American Heart Association meeting held in November 2005, relevant to the pathophysiology, prevention and treatment of heart failure. All reports should be considered as preliminary data, as analyses may change in the final publication. In REPAIR-AMI an improvement in ejection fraction was observed in post-MI patients following infusion of bone marrow stem cells. However, the ASTAMI study showed no benefit of stem cell implantation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
151
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(158 citation statements)
references
References 14 publications
(17 reference statements)
3
151
1
3
Order By: Relevance
“…However, a recent clinical trials update from the American Heart Association [Cleland et al, 2006] reports no benefit of stem cells implantation in the ASTAMI study and a small but significant benefit in REPAIR-AMI.…”
mentioning
confidence: 99%
“…However, a recent clinical trials update from the American Heart Association [Cleland et al, 2006] reports no benefit of stem cells implantation in the ASTAMI study and a small but significant benefit in REPAIR-AMI.…”
mentioning
confidence: 99%
“…Other vasodilators, such as calcium sensitizers, were received initially with much promise, although subsequent properly controlled studies did not duplicate the initial small randomized studies (45).…”
Section: Intravenous Inotropic Therapymentioning
confidence: 99%
“…There are no placebo-controlled trials assessing dobutamine efficacy in AHF, but it is clearly associated with increased incidence of arrhythmias (168). Levosimendan, a calcium-sensitizing inodilator, has been reported to reduce mortality compared with dobutamine and placebo (169). In the Randomized Multicenter Evaluation of Intravenous Levosimendan Efficacy II (REVIVE-II) trial (169), levosimendan showed modest benefit over placebo, but there was more hypotension and atrial fibrillation, and mortality at 90 days was higher.…”
Section: Medical Treatment Of Ahf Recommendationsmentioning
confidence: 99%
“…In the Randomized Multicenter Evaluation of Intravenous Levosimendan Efficacy II (REVIVE-II) trial (169), levosimendan showed modest benefit over placebo, but there was more hypotension and atrial fibrillation, and mortality at 90 days was higher. In the Survival of Patients with Acute Heart Failure in Need of Intravenous Inotropic Support (SURVIVE) study (169), there was a trend to early benefit with levosimendan over dobutamine that was not evident past the period of hemodynamic efficacy of the drug; there was more atrial fibrillation, and mortality was comparable at the end of the study (169). Because there was no placebo-treated arm in this study, although levosimendan appeared to have better efficacy and safety than dobutamine, this is not to say that it is superior to placebo.…”
Section: Medical Treatment Of Ahf Recommendationsmentioning
confidence: 99%